The investigation of opening modes of head and neck thermoplastic mask for radiotherapy based on finite element analysis - Guobao Pang; Ying Lu; Yannan Xu; Qiaoyu Meng; Jianbo Song (Radiation Oncology)
Abstract Radiotherapy is a crucial treatment modality for head and neck tumors. Precise patient positioning is vital for ensuring the reproducibility and accuracy of the treatment. Clinically, thermoplastic head and neck masks are used for positioning, and patients often require openings in these masks. However, the relationship between opening locations and the fixation effectiveness of the masks has not been thoroughly studied. This study reconstructs a patient’s imaging data to create finite element models with 10 different opening patterns. By assigning various thicknesses and material properties to the fixation masks, we analyzed the displacement distribution of different opening models under diverse loading conditions. The results indicate that the opening location significantly impacts fixation effectiveness under different loading conditions. In particular, the opening in the forehead area has the most significant impact on the fixation effect of the mask near the region of interest (ROI). Therefore, in clinical practice, the design of openings in the forehead area should be carefully considered. This study provides valuable insights into the fixation effectiveness of thermoplastic masks and serves as a reference for future personalized positioning treatments.